2019
DOI: 10.1111/jabr.12163
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of telephone‐delivered cognitive‐behavioral‐based physical therapy for patients with traumatic lower extremity injury

Abstract: Purpose To determine feasibility and acceptability of a telephone‐based Cognitive‐Behavioral‐Based Physical Therapy program for patients following traumatic lower extremity injury (CBPT‐Trauma). Methods Patients were screened for high psychosocial risk factors and then completed the 6‐week CBPT‐Trauma program. Physical function, pain, and psychosocial outcomes were assessed at baseline and 6‐months follow‐up. Descriptive statistics assessed change in outcomes. Results Recruitment rate was 59%. Twenty‐seven pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…This trial builds off previous pilot testing of the CBPT-Trauma program, which found the program to be feasible in recruitment and screening rates and acceptable based on patient satisfaction and improvements in patientreported physical function. 17 Early testing of the CBPT-Trauma program supports screening and a targeted approach to care, which is consistent with previous studies of psychosocial interventions in the trauma population. 13,47,48 Overall, our interventional approach (CBPT-Trauma) is designed to empower patients to return to a productive life both inside and outside the home and ultimately improve their general physical and mental health.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This trial builds off previous pilot testing of the CBPT-Trauma program, which found the program to be feasible in recruitment and screening rates and acceptable based on patient satisfaction and improvements in patientreported physical function. 17 Early testing of the CBPT-Trauma program supports screening and a targeted approach to care, which is consistent with previous studies of psychosocial interventions in the trauma population. 13,47,48 Overall, our interventional approach (CBPT-Trauma) is designed to empower patients to return to a productive life both inside and outside the home and ultimately improve their general physical and mental health.…”
Section: Discussionsupporting
confidence: 81%
“…The duration of the programs and each session was established during proof-of-concept and pilot test work and has been found to be acceptable to patients and effective for clinically meaningful treatment effects. 17,25 At 5 and 9 months post-initial hospital discharge, booster sessions were conducted with both groups. During the booster sessions, the CBPT-Trauma participants reviewed their recovery plan and discussed utilization of their self-management strategies and the education participants had a general check-in call to review the educational material.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two licensed physical therapists with >10 years of experience treating patients with musculoskeletal pain delivered the programs remotely by telephone to all patients in the treatment group. The CBPT for trauma survivors (CBPT-Trauma) intervention in this study was adapted from CBT-based programs for chronic pain and spine surgery [23][24][25][26][27][28][29][39][40][41] by emphasizing a patient-oriented cognitive-behavioral self-management approach to decrease pain and increase physical function 23 . The education control program consisted of the provision and discussion of written education materials typically provided by the physical therapy care team during postoperative recovery as well as scheduled interactions with a physical therapist, during which these materials were reviewed 35 .…”
Section: Interventionsmentioning
confidence: 99%